The value of the expression when g = -2 is -1
<h3>How to simplify the expression</h3>
Given the expression;
(5+2g)exp5
(5+2g)^5
For g = -2
Let's substitute the value of g in the expression
= ( 5 + 2 ( -2) ) ^5
Expand the bracket
= ( 5 - 4) ^ 5
Find the difference
= (-1) ^5
= -1
Thus, the value of the expression when g = -2 is -1
Learn more about algebraic expressions here:
brainly.com/question/4344214
#SPJ1
In step one, you are supposed to add 25 to both sides, because if you just subtract, it would be -5x-50=53
Answer: SEE EXPLANATION (en ingles)
Step-by-step explanation:
A binomial is an algebraic expression of the sum or the difference of two terms.
En espanol: Un binomio es una expresión algebraica de la suma o la diferencia de dos términos.
Hello!
This triangle is currently located in Quadrant 1. If it is rotated 90 degrees counter-clockwise around the origin, it will end up in Quadrant 2. The formula for this is seen below.
(x,y)⇒(-y,x)
We will do this to each point and get our final points.
(4,4)⇒(-4,4)
(4,1)⇒(-1,4)
(2,1)⇒(-1,2)
Therefore, the final points of our rotated triangle are (-4,4), (-1,4) and (-1,2).
I hope this helps!
Please find full question attached Answer:
Barbara is not more well off as the typical individual has a higher well being score
Explanation:
please find explanation attached